Chorea, polycythaemis, and cyanotic heart disease. Issue 8 (August 1975) - Edwards, P D; Prosser, R; Wells, C E
Abstract : Two cases of polycythaemic chorea are described, both of which were complicated by severe heart disease. The first was a child with patent ductus arteriosus and coarctation of the aorta causing severe cyanosis and secondary polycythaemia. Chorea began intermittently at an early age, becoming continuous by his fifth birthday. The second was a middle-aged male with tight mitral stenosis and a story of paralytic chorea in his teens. Polycythaemia rubra vera was eventually diagnosed two years after mitral valvotomy, some seven years after the onset of chorea.